PELATIHAN KONSELOR PENINGKATAN KETERAMPILAN KONSELING KESEHATAN REPRODUKSI REMAJA BERKEBUTUHAN KHUSUS PADA GURU SLB NEGERI 1 DENPASAR - I.G.A. Pramitaresthi; I.G.N. Pramesemara; I.A. Sanjiwani; L.M. Puspita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Sexual education for adolescents with special needs is very important. Basically, teenagers with special needs do not have enough courage to tell stories and lack the ability to find information that can be obtained from articles or books. Based on philosophical and juridical, sex education is a preventive effort so that every teenager with special needs can recognize, understand and deal with biological developments and changes. In addition, sex education for teenagers with special needs also aims to guide them to respect the sexual behavior of others and not be trapped in deviant sexual behavior and not get sexual violence and harassment from others. Teachers are responsible for teaching their independence in schools. Therefore, there is a need for training for teachers so that later they can become counselors for adolescents with special needs who need reproductive health information. The purpose of this activity is to provide knowledge and train teachers' skills to provide sexuality information to adolescents with special needs. The method of this activity is in the form of lectures, question and answer discussions and the provision of pre-test and post-test questionnaires which will be held on October 7, 2021 online using the Zoom application which was attended by teachers and then continued with consultations through the Whatsapp group. The results of the questionnaire analysis showed an increase in participants' knowledge after being given training. The conclusions and implications are expected that after this, teachers can provide reproductive health and sexuality education to adolescents with special needs. Keywords: Teachers, Counselors, Reproductive Health, Youth with Special Needs